要写出过程:(1)(-11)-(-6)+(-5)-(-3)(2)0-21又2/3+(+3又3/4)-(-2/3)-(-0.25)

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 17:49:06
要写出过程:(1)(-11)-(-6)+(-5)-(-3)(2)0-21又2/3+(+3又3/4)-(-2/3)-(-0.25)要写出过程:(1)(-11)-(-6)+(-5)-(-3)(2)0-21

要写出过程:(1)(-11)-(-6)+(-5)-(-3)(2)0-21又2/3+(+3又3/4)-(-2/3)-(-0.25)
要写出过程:(1)(-11)-(-6)+(-5)-(-3)(2)0-21又2/3+(+3又3/4)-(-2/3)-(-0.25)

要写出过程:(1)(-11)-(-6)+(-5)-(-3)(2)0-21又2/3+(+3又3/4)-(-2/3)-(-0.25)
(1)(-11)-(-6)+(-5)-(-3)
=-11+6-5+3
=-7
(2)0-21又2/3+(+3又3/4)-(-2/3)-(-0.25)
=-21又2/3+3又3/4+2/3+1/4
=-21+4
=-17